2010
DOI: 10.1002/app.32165
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polystyrene‐b‐poly(ethylene oxide) diblock copolymer and investigation of its micellization behavior in water

Abstract: ABSTRACT:The recent studies deal with a diblock copolymer, polystyrene-poly(ethylene oxide). Infrared spectroscopy, proton resonance spectroscopy ( 1 H-NMR), and laser light scattering techniques have been used to characterize the polymer. It has been concluded that the sample investigated is diblock copolymer polystyrene-poly(ethylene oxide) having molecular mass 1.656 Â 10 4 g/mol and blocks ratio 1 : 2. The micellization behavior is explored through 1 H-NMR, laser light scattering, light absorption, surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The CMC of those block copolymers, with similar molar ratio of hydrophile to hydrophobe compared to this study, was reported to be 4 × 10 −4 M . Another study with PS‐ block ‐poly(ethylene oxide) at higher molecular weights (16.2 kg mol −1 ) measured the CMC to be 55 × 10 −4 M . As expected, the block copolymers in this study exhibit lower CMCs due to their molecular weight being up to 2.5 times higher.…”
Section: Resultssupporting
confidence: 78%
“…The CMC of those block copolymers, with similar molar ratio of hydrophile to hydrophobe compared to this study, was reported to be 4 × 10 −4 M . Another study with PS‐ block ‐poly(ethylene oxide) at higher molecular weights (16.2 kg mol −1 ) measured the CMC to be 55 × 10 −4 M . As expected, the block copolymers in this study exhibit lower CMCs due to their molecular weight being up to 2.5 times higher.…”
Section: Resultssupporting
confidence: 78%
“…Peaks at 768 cm −1 (benzene bending) and 1608 cm −1 , 1496 cm −1 and 1454 cm −1 (benzene ring stretching), weak overtone and combination bands in the range of 1655–2000 cm −1 all be attributed to polystyrene24. The features at 1108 cm −1 (C-O-C stretch), 929 cm −1 (CH 2 PEO rocking modes), and 1752 cm −1 and 1719 cm −1 (C = O stretches of the ester and keto group respectively) as well as peaks at 2927 cm −1 and 2854 cm −1 (CH 2 PEO stretching modes) can all be assigned to the PEO block25. A broad band in the range of 3300–3700 cm −1 also appears due to alcohol type O-H stretching vibrations and/or atmospheric moisture.…”
Section: Resultsmentioning
confidence: 90%
“…Diblock co‐oligomers with various hydrophobic block lengths ( m PEG 16 ‐ b ‐PS 2 , m PEG 16 ‐ b ‐PS 4 , and m PEG 16 ‐ b ‐PS 6 ) were produced and their self‐assembly studied. While the synthesis and the self‐assembly properties of PEG‐ b ‐PS (and PEO‐ b ‐PS) have been explored,1, 26, 53–62 the study presented here is the first to synthesize and self‐assemble such short chain lengths of m PEG‐ b ‐PS diblock co‐oligomers. The final product, m PEG‐ b ‐PS, has a butyltrithiocarbonate end group at the PS end, and therefore will be presented in the core of the nanostructures resulting from micellization in aqueous media.…”
Section: Resultsmentioning
confidence: 99%